Interpersonal grammar : systemic functional linguistic theory and description - Martin, J. R., 1950-; Quiroz, Beatriz, 1976-; Figueredo, Giacomo (Cambridge ; New York, NY : Cambridge University Press, 2021)
This pioneering volume lays out a set of methodological principles to guide the description of interpersonal grammar in different languages. It compares interpersonal systems and structures across a range of world languages, showing how discourse, interpersonal relationships between the speakers, and the purpose of their communication, all play a role in shaping the grammatical structures used in interaction. Following an introduction setting out these principles, each chapter focuses on a particular language - Khorchin Mongolian, Mandarin, Tagalog, Pitjantjatjara, Spanish, Brazilian Portuguese, British Sign Language and Scottish Gaelic - and explores mood, polarity, tagging, vocation, assessment and comment systems. The book provides a model for functional grammatical description that can be used to inform work on system and structure across languages as a foundation for functional language typology.
Title from publisher's bibliographic system (viewed on 21 May 2021).
Keywords: Functionalism (Linguistics); Interpersonal communication; Grammar, Comparative and general; Systemic grammar